Is the restoration of bowel sounds a prerequisite for initiating enteral feeding following pediatric laparotomy? A randomized control trial - N.T. Abdulraheem; A.A. Nasir; L.O. AbdurRahman; A.O. Oyinloye; M.A. Alada; M.O. Olanrewaju; D.C. Nwosu; J.O. Adeniran (Elsevier, 2024)
Introduction: Enteral nutrition is the mainstay of nutritional support in surgical patients. Ileus is the temporary inhibition of peristalsis. Primary post-operative ileus (PPI) occurs postoperatively; thence patients are traditionally kept on nil per oris (NPO) until PPI resolves, due to safety concerns. This study aims to determine the necessity or otherwise of this practice in paediatric surgical patients. Materials and methods: A prospective, randomized control trial, in patients younger than 15 years. The early feeding group (EFG) commenced enteral feeding on the first post-operative day while controls commenced feeding after resolution of PPI. Data was analyzed using SPSS version 20.0, P ≤ 0.05 was regarded as significant. The primary outcome was tolerability of enteral feeds while secondary outcomes were complication rates, time to full enteral diet, and duration of hospital stay. Results: There were 56 patients, 28 in each study group. Tolerability of oral feeds at initial commencement was similar in both groups (24 (85.7%) EFG versus 27 (96.4%) controls P = 0.16). Full enteral feeding was achieved faster in EFG than in controls (71.1 ± 28.7 hours versus 92.5 ± 31.4 hours, p=0.011). Post-operative hospital stay was shorter in EFG than controls (7.46 ± 3.8 days versus11.1 ± 5.2 days, p=0.009). Conclusions: Early enteral feeding was well tolerated, brought about a faster return to a full enteral diet, and shorter post-operative hospital stay, it also did not cause a higher complication rate. Therefore, delaying feeding until the resolution of PPI after laparotomy appears unnecessary.